Platelet-Derived Microparticles From Obese Individuals: Characterization of Number, Size, Proteomics, and Crosstalk With Cancer and Endothelial Cells - Grande, Rosalia; Dovizio, Melania; Marcone, Simone; Szklanna, Paulina B.; Bruno, Annalisa; Ebhardt, H. Alexander; Cassidy, Hilary; Ní Áinle, Fionnuala; Caprodossi, Anna; Lanuti, Paola; Marchisio, Marco; Mingrone, Geltrude; et al. (Frontiers in Pharmacology, 2019)
Rationale. Obesity is a risk factor for atherothrombosis and various cancers. However, the mechanisms are not yet completely clarified. Objectives. We aimed to verify whether the microparticles (MPs) released from thrombin-activated platelets differed in obese and nonobese women for number, size, and proteomics cargo and the capacity to modulate in vitro the expression of (i) genes related to the epithelial to mesenchymal transition (EMT) and the endothelial to mesenchymal transition (EndMT), and (ii) cyclooxygenase(COX)-2 involved in the production of angiogenic and inflammatory mediators. Methods and Results. MPs were obtained from thrombin activated platelets of four obese and their matched nonobese women. MPs were analyzed by cytofluorimeter and protein content by liquid chromatography-mass spectrometry. MPs from obese women were not different in number but showed increased heterogeneity in size. In obese individuals, MPs containing mitochondria (mitoMPs) expressed lower CD41 levels and increased phosphatidylserine associated with enhanced Factor V representing a signature of a prothrombotic state. Proteomics analysis identified 44 proteins downregulated and three upregulated in MPs obtained from obese versus nonobese women. A reduction in the proteins of the a-granular membrane and those involved in mitophagy and antioxidant defenses-granular membrane was detected in the MPs of obese individuals. MPs released from platelets of obese individuals were more prone to induce the expression of marker genes of EMT and EndMT when incubated with HT29 human colorectal cancer cells and human cardiac microvascular endothelial cells(HCMEC), respectively. A protein, highly enhanced in obese MPs, was the pro-platelet basic protein with pro-inflammatory and tumorigenic actions. Exclusively MPs from obese women induced COX-2 in HCMEC. Conclusions. Platelet-derived MPs of obese women showed higher heterogeneity in size and contained different levels of proteins relevant to thrombosis and tumorigenesis. MPs from obese individuals presented enhanced capacity to cause changes in the expression of EMT and EndMT marker genes and to induce COX-2. These effects might contribute to the increased risk for the development of thrombosis and multiple malignancies in obesity. Clinical Trial Registration number: Clinicaltrials.gov Registration number NCT01581801